The Influence Of Work Discipline And Work Motivation On Job Satisfaction With Employee Performance As Mediation At PT. Jagat Sejahtera Abadi Kota Bekasi - Dodi Rustandi; Anna Wulandari; Sarwo Edy (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2024)
This study aims to determine The Influence Of Work Discipline And Work Motivation On Job Satisfaction With Employee Performance As Mediation At PT. Jagat Sejahtera Abadi Kota Bekasi. Respondents of this study were 54 respondents and this study used a quantitative approach with the SmartPLS 3.0 data processing application. The results of this study found that 1. There is a significant effect of work discipline on employee performance Employees, 2. Work motivation has no significant effect on employee performance, 3.Employee performance has a significant effect on job satisfaction, 4. Work discipline has a significant effect on job satisfaction, 5. Work motivation has no significant effect on employee performance, 6. Work discipline has a significant effect on job satisfaction through employee performance, 7. Work motivation has no significant effect on job satisfaction through employee performance.